2018
DOI: 10.3329/pa.v29i1.37480
|View full text |Cite
|
Sign up to set email alerts
|

Present status, problems and prospect of fish farming at Gazipur Sadar upazila in Bangladesh

Abstract: The present study was conducted to reveal the present scenario, problems and the prospect of fish farming of Gazipur Sadar upazila Bangladesh. The primary data were collected through field survey, questionnaire interview and focus group discussion from the fish farmers of several villages and urban areas of the upazila. Secondary data were collected from the Department of Fisheries and aquaculture extension section. Gazipur Sadar upazila has 14462.42 ha potential fisheries resources of which floodplains, seaso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 8 publications
6
15
0
Order By: Relevance
“…Almost all farmers reported that low price of fish was the main problems of fish farming. Similar types of pond farming constraints were found by some authors (Jahan et al 2015;Shamsuzzaman et al 2017;Das et al 2018). In conclusion, high value fishes are promising aquaculture species in Bangladesh.…”
Section: Discussionsupporting
confidence: 85%
“…Almost all farmers reported that low price of fish was the main problems of fish farming. Similar types of pond farming constraints were found by some authors (Jahan et al 2015;Shamsuzzaman et al 2017;Das et al 2018). In conclusion, high value fishes are promising aquaculture species in Bangladesh.…”
Section: Discussionsupporting
confidence: 85%
“…Evidence shows that 73% of rural households are engaged in some form of aquaculture across the country (Mazid 1999); 1.2 million people are directly employed, and 12 million more are indirectly engaged in fishery-related activities (Dey et al 2008). Das et al (2018) found that over 71% of total sampled farmed fish producers had either a primary or secondary education level. Their study also showed that farmers' education level affected the utilization of ponds and fish production (Khan 1986).…”
Section: The Aquaculture Market In Bangladeshmentioning
confidence: 99%
“…These included lack of technical knowledge; joint ownership of ponds; costly fish feed and other necessary inputs; inadequate knowledge about economics; insufficient quality of fingerlings; and limited access to credit options (Ahmed and Rab 1992;Gupta, Ahmed, and Bimbao 1992;Gupta et al 1999;Ahmed and Rab 1994;Gupta and Rab 1994;Lewis 1997;Chowdhury and Maharjan 2001;Thompson, Sultana, and Nuruzzaman Md 2005;ADB 2005). In a recent study, Das et al (2018) found that 80% of farmers do not receive any scientific aquaculture training, learning about fish farming from their ancestors or neighbors in an unscientific way. Another problem of Bangladesh's aquaculture is that even though pond size and depth affect the efficiency of fish production positively (Khan 1986), most aquaculture ponds in Bangladesh are small (e.g., 1-4 Decimal), with only 17.27% of ponds relatively large.…”
Section: The Aquaculture Market In Bangladeshmentioning
confidence: 99%
“…Hence, the meat of broiler chickens, egg, and milk may contain antimicrobial residues which increase the possibility of developing resistant bacteria ( Hasan et al, 2012 ; Hassan et al, 2014 ) which represents a serious threat to public health ( Sachi et al, 2019 ). Aquaculture such as commercial fish and prawn farming is popular in Bangladesh as a source of low-cost protein to underprivileged groups of the society ( Ahmed et al, 2008 ; Das et al, 2018 ). Antimicrobial agents are also used as feed additives in fish farming triggering antimicrobial resistant bacteria in water bodies and contaminating the aquaculture and the environment ( Ahaduzzaman et al, 2014 ; Hassan et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%